PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL, DAN KECERDASAN SPIRITUAL TERHADAP KINERJA KARYAWAN - Yesi Novita Novita; Khairul Bahrun (UM. Bengkulu, 2026)
This study aims to determine the influence of intellectual intelligence, emotional intellegence, and spiritual intelligence on the performance of my lova Bengkulu employees. This type oof research is a quantitative tipe of research, the population of this research is MY Lova Bengkulu employees as the research object. The data collection techniques used are observasition, interviews and questionnaires. Meanwhile, the data analysis technique uses descriptive analysis, multiple linear regression analysis wiith hipothesis testing. The results of this study indicatethat intellectual inteligence has a positive effect oon the performance of My Lova Bengkulu. This means that the higher the level of intellectual intelligence of employees, the higher the level of employee performance. Emtional intelligence has a positive influence on the performance of My Lova Bengkulu emplloyees. The better the level of emotional intelligence of employees, the highr the level of emloyee performance. Spiritual intelligence has a positive influence on the performance of My Lova Bengkulu employees. The better the level ofemployee spiritual intelligence, the higher the employee performance. Intellctual intelligence, emotional intelligence, and spiritual intelligence simultaneously or together have a positive and significant influence on the performance of My Lova Bengkulu employees. This means that if the level of intellectual intelligence, emotionlintelligence, and spiritual intelligence of My Lova Bengkulu employees is high, it will improve the performance of My Lova Bengkulu employees. Keywords : intellectual intelligence, emotional intelligence, spiritual intelligence, employee performance